Guitarras elétricas, cabeludos, transviados e iê-iê-iê : Aracaju no embalo da Jovem Guarda (1965 – 1969) - Gomes, Wilian Siqueira Santos (2019)
This work presents a historical analysis of the cultural scene of Aracaju in the second half of the 1960s, focusing on a part of the local youth involved with the aesthetics of Rock'n'roll. Inspired by the Beatles and the artists associated with the Jovem Guarda, boys and girls began playing electric instruments and were soon packing the Sergipe capital to the rhythm of iê-iê-iê. It brings an understanding of the reception by young people of information about the new rhythm, their musical learning, the formation of musical ensembles, the rise to the stages and its repercussion, the decline of popularity, the changes of style and the closure of their activities. They are objects of analysis also the reactions of the Aracaju society when witnessing young people with big hair and exotic clothes to appear in their social clubs, cinemas, gymnasiums and radio programs. The time cut chosen, from 1965 to 1969, coincides with a period of restrictions on freedom of expression where the State exerted strict control over any activity that could express a challenge to the current models. Through the methodology of oral history, interviews with participants of the movement were carried out. Documents relating to the control of public amusements and the careers of the musicians involved, periodicals and photographs complete their body from sources. The theoretical matrix of the research was based on the new cultural history, with its possibilities of interpretation of human actions through practices and representations of objects and symbols, for the apprehension of meanings and processes of creation, distribution and reception of cultural elements. As a result, the research presents a contribution to the history of cultural production in Sergipe, unveiling, in an almost unprecedented way, the participation of the youth of its capital in a musical and behavioral movement of worldwide repercussion, even with the restrictions imposed by the installed dictatorial regime in the country. At the same time, it shows the peripheral position of Aracaju in the spectrum of the Brazilian cultural industry, still in development stage, revealing the difficulty of penetration of the music produced in Sergipe in the national market.